THE EFFECT OF A SITUATIONAL LEADERSHIP STYLE AND THE APPLICATION OF ACCOUNTING INFORMATION SYSTEMS TO FRAUD ON VILLAGE FUND MANAGEMENT IN TANGERANG DISTRICT - Yudha Brata, Tubagus (Dinasti Publisher, 2021)
This study is motivated by the many cases of corruption, especially when the management of village funds began to be implemented. This type of quantitative research with survey techniques using closed questionnaire 5 Likert scale choices. Affordable population 224 people. A sample of 90 people was taken by simple random sampling. The results showed: 1) Situational leadership style in the Good category. 2) Application of AIS in the Good category. 3) Management of village funds has the potential to cause fraud. 4) Situational leadership style has a significant effect on fraud with a negative correlation that is if the situational leadership style increases, the potential for fraud decreases. 5) The application of SIA has a significant effect on Fraud, with a negative correlation that is if the application of AIS is high, the potential for fraud is reduced. 6) Situational leadership style and application of AIS together influence fraud.